Efektivitas mandatory spending fungsi kesehatan dan dampaknya terhadap derajat kesehatan masyarakat di Provinsi Papua - Ahyuni, Siti; Sutjipto, Hady (Social, Ecology, Economy for Sustainable Development Goals Journal, 2023)
The effectiveness of mandatory spending on health functions is a form of fiscal policy instrument which aims to realize the development of health status in Papua Province. This research aims to analyze the development and influence of the effectiveness of mandatory spending allocations for health functions on the development of public health status in 28 Regencies/Cities of Papua Province for the 2017-2019 period. Analysis of mandatory spending for district/city health functions in Papua Province includes health spending, special autonomy funds and general allocation funds. The method used in this research is a quantitative approach using panel data regression analysis with the Fixed Effect Model (FEM). The results of this research show that simultaneously, the mandatory spending variable has a significant effect on the level of public health in the District/City of Papua Province, while partially, the variable health spending and general allocation funds have a significant effect on the health level indicators, in contrast to the particular autonomy fund variable which does not have a significant influence on the level of public health in the District/City of Papua Province.